1972
DOI: 10.1152/ajplegacy.1972.223.5.1097
|View full text |Cite
|
Sign up to set email alerts
|

Species difference in carotid body response of cat and dog to dopamine and serotonin

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 0 publications
5
38
0
Order By: Relevance
“…MATSUMOTO et al (1980a) already ascertained that in the rabbit, DA in a low dose had a potent chemoreceptor depressing effect leading to marked decreases in respiratory rate and VT and these effects were not evoked after the section of the CNS. There is other evidence that in the cat, an intracarotid injection of DA led to an immediate inhibition of ventilation through a carotid chemoreflex because it produced no response when the CSN was sectioned (BLACK et al, 1972). Therefore, it may be more conceivable that DA exerts its inhibitory effect on respiratory muscle activity through a carotid chemoreflex.…”
Section: Discussionmentioning
confidence: 99%
“…MATSUMOTO et al (1980a) already ascertained that in the rabbit, DA in a low dose had a potent chemoreceptor depressing effect leading to marked decreases in respiratory rate and VT and these effects were not evoked after the section of the CNS. There is other evidence that in the cat, an intracarotid injection of DA led to an immediate inhibition of ventilation through a carotid chemoreflex because it produced no response when the CSN was sectioned (BLACK et al, 1972). Therefore, it may be more conceivable that DA exerts its inhibitory effect on respiratory muscle activity through a carotid chemoreflex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that noradrenaline in the dog causes an increase in chemoreceptor discharge (Joels & White, 1968;Black et al, 1972). When CO2 and noradrenaline were given simultaneously to the donor dog a greater vasodilation in the recipient cerebral circulation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In the dog noradrenaline has been shown to cause an increase in the afferent discharge from the carotid body chemoreceptors (Black, Comroe & Jacobs, 1972). Some of the changes observed in the cerebral circulation following noradrenaline administration could, therefore, not only be due to a direct effect on the vessel wall, or secondary to blood pressure changes but could possibly be caused by activation of the carotid body chemoreceptors. Some years ago we demonstrated that hypercapnia attenuated the vasodilator response of the cerebral circulation to an isoprenaline infusion (Xanalatos & James, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…~ere is also convincing evidence that these substances are contained primarily within the glomus, or Type I, cells of the carotid body [6,7]. Electrophysiological and pharmacological studies in the cat [23,24,28], dog [4] and rabbit (Monti-Bloch and Eyzaguirre, pets. comm.)…”
mentioning
confidence: 99%
“…However, the precise mode of action of DA in carotid body chemoreception remains to be elucidated, and there is now evidence that the effe~ ; of exogenous DA on the chemosensory discharges of the carotid nerve may be species dependent. Thus, in the cat, DA inhibits the chemosensory discharges [23,24,28], but appears to be stimul~tory in the dog [4] and rabbit (Monti-Bloch and Eyzaguirre, pers. comm.).…”
mentioning
confidence: 99%